Manajemen Kurikulum Program Tematik dalam Mengembangkan Kemampuan Intelektual Peserta Didik di SDLB Dharma Wanita Ujung Pangkah Gresik - Nurus Saidatul Mafakhir; Muslih Muslih; Muh. Hasyim Rosyidi; Muhammad Haris; Hidayatul Mufidah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2022)
Focus Study this is for understand about management curriculum thematic at SDLB Dharma Wanita Ujung Pangkah Gresik in effort develop ability intellectuals participant educate . Learning thematic in SLB same with school general , which Becomes difference is teacher must capable adapt condition child , if on normally they led for complete target but in SLB is teacher teach slowly until they capable control lesson , because participant educate no easy in understand eye lesson so teacher must have method creative and unique so that participant educate easy in understand . Study this aim answer a number of Formula Problem , ie : 1. How Management Curriculum program thematic in develop ability intellectual participant educate at SDLB Dharma Wanita Ujungpangkah Gresik, 2. How factor supporters and inhibitor Management curriculum program thematic in develop ability intellectual participant educate at SDLB Dharma Wanita Ujungpangkah Gresik.? Method study which used in study this is with study descriptive qualitative . In collection the data use method observation , interview deep as well as documentation . With use technical analysis miles model ie reduction data, presentation data and withdrawal conclusion . Results in study this , First , that Management Curriculum at SDLB Dharma Wanita Ujungpangkah Gresik use Curriculum 2013, Stages which held in Thing the ie 1) Planning curriculum thematic SDLB . 1. Do assessment , 2. Make device learning 2) Organizing Curriculum thematic is 1. forming structure organization 2. Share Duty teacher 3. Share timetable lesson corresponding structure curriculum from government 3) Implementation curriculum thematic is 1. implementation curriculum customized with device learning 2. Implementation curriculum must customized with circumstances student Which one they have difference disabled , so that they capable follow learning and practice student so that capable life independent , 3) Evaluation ie with 1. Evaluation repair plan 2. Evaluation results learning , second , a number of factor inhibitor ie Condition the crew diverse , Competence that teacher diverse , Lack of cooperation by people old crew with party school so that still there is a number of difference purpose . Third Factor supporters 1. party school get book hold on special from government , 2. Party school support media and tool learning which needed based on with type disabled participant educate the . 3. How strong connection Among head school and teachers at SDLB Dharma Wanita as well supported by Public around and also party from education and districts . As for suggestions from results study the recommended for in the future SDLB Dharma Wanita Ujungpangkah Gresik capable work same with people old in process learning student so that capable reach purpose which wanted good that from parent and also from school